2009
DOI: 10.2175/193864709793901301
|View full text |Cite
|
Sign up to set email alerts
|

Denitrification Rates: Sampling, Modeling and Design Considerations

Abstract: Biological denitrification of wastewater has been a topic of interest for several decades; however, recent nutrient reduction initiatives and the need to achieve limit-of-technology (LOT) effluent quality have renewed interest in denitrification rate research. Since readily-biodegradable chemical oxygen demand (rbCOD) drives rapid denitrification, it is essential for design efforts to include raw influent and primary effluent sampling, for different seasons if possible. However, the influent rbCOD/TKN ratio is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Dold et al [10] used modeling to design optimal batch tests procedures, and to estimate the maximum specific growth rate of heterotrophs under anoxic conditions. Phillips et al [11] used a dynamic model to optimize the mixed liquor recycle rate and studied factors that affected nitrogen removal, including the influent wastewater readily biodegradable COD/N ratio and acetate addition. The strategies and calculations of the optimum COD/N ratios were investigated by FilaliMeknassi et al [12] (in sequencing batch reactor (SBR)) and Latimer et al [13] (in continuous flow reactor).…”
Section: Resultsmentioning
confidence: 99%
“…Dold et al [10] used modeling to design optimal batch tests procedures, and to estimate the maximum specific growth rate of heterotrophs under anoxic conditions. Phillips et al [11] used a dynamic model to optimize the mixed liquor recycle rate and studied factors that affected nitrogen removal, including the influent wastewater readily biodegradable COD/N ratio and acetate addition. The strategies and calculations of the optimum COD/N ratios were investigated by FilaliMeknassi et al [12] (in sequencing batch reactor (SBR)) and Latimer et al [13] (in continuous flow reactor).…”
Section: Resultsmentioning
confidence: 99%
“…The same authors demonstrated the effect of differences in denitrification kinetics for two external carbon sources, methanol and a commercial compound (MicroC TM , Environmental Operating Solutions, Inc., Bourne, Massachusetts), on the anoxic volumes needed and nitrogen removal performance for the modified Ludzak-Ettinger and 4-stage Bardenpho BNR process configurations. Phillips et al (2009) used a dynamic model to optimize the mixed liquor recycle rate and studied factors that affected nitrogen removal, including the influent wastewater readily biodegradable COD/N and acetate addition. Strategies for dosing external carbon sources and calculations of the optimum COD/N were investigated by Latimer et al (2009) (sugar addition to a continuous flow reactor) and Filali-Meknassi et al (2005) (acetate addition to a sequencing batch reactor).…”
Section: Introductionmentioning
confidence: 99%
“… The acetate consumed by PAOs was corrected by subtracting the stoichiometric utilization of acetate by denitrification (nitrite accumulations were considered). The correction was made based on a theoretical COD/NOx‐ N ratio of 3.5 for acetate (McCarthy, Beck, & Amant, , Phillips et al, ). …”
Section: Resultsmentioning
confidence: 99%